Numerical Simulation of Tsunami Hazard Mitigation by Mangrove Forest in North Coast Bali, Indonesia - Gunawan, Putu Harry (Jurnal Matematika; Vol 5 No 1 (2015)DO - 10.24843/JMAT.2015.v05.i01.p51, 2015)
Mangrove forest or known as bakau forest is important forest as a natural wave barrier or tsunami wave mitigation. Some advantages of mangrove forest to reduce the water waves are already studied. Mangrove forest in north coast of Bali’s island, Buleleng regency, Indonesia is in damaged condition. The aim of this paper is to present the importance of mangrove forest as the water wave mitigation in numerical simulation point of view. Moreover, the results also show the effect of tsunami propagation to the coastal area with and without mangrove resistance. Here, the nonlinear shallow water equations are used to govern the model of numerical simulation.
Keywords: Numerical simulation, Tsunami, Mangrove, Shallow water equations